Seasonal and annual variations in the pollination efficiency of a pollinator community of Dictamnus albus L. (7th December 2015) - Fisogni, A.; Rossi, M.; Sgolastra, F.; Bortolotti, L.; Bogo, G.; de Manincor, N.; Quaranta, M.; Galloni, M.
Abstract: The interplay between insect and plant traits outlines the patterns of pollen transfer and the subsequent plant reproductive fitness. We studied the factors that affect the pollination efficiency of a pollinator community of Dictamnus albus L. by evaluating insect behaviour and morphological characteristics in relation to flowering phenology. In order to extrapolate the pollinator importance of single taxa and of the whole pollinator guild, we calculated an index distinguishing between potential (PPI) and realized (RPI) pollinator importance. Although the pollinator species spectrum appeared rather constant, we found high intra‐ and inter‐annual variability of pollinator frequency and importance within the insect community. Flower visitation rate strictly depended on insect abundance and on the overlap between their flying period and flower blooming. All the pollinators visited flowers from the bottom to the top of the racemes, excluding intra‐plant geitonogamous pollination, and most of them showed high pollen fidelity. Only medium large‐sized bees could contact the upward bending stiles while feeding on nectar, highlighting a specialisation of the plant towards bigger pollinators. Moreover, we found evidence of functional specialisation, since all pollinators were restricted to a single taxonomic group (order: Hymenoptera; superfamily: Apoidea). Both the PPI and RPI indices indicate Habropoda tarsata as the most important pollinator of D. albus . Following hand cross‐pollination experiments we revealed the presence of pollination limitation in 1 of the 3 years of field study. We discuss this result in relation to flowering abundance and to possible mismatches of phenological periods between plants and insects.